Development and Characterization of Andean Pseudocereal Bars Enriched with Native Collagen from Pota (Dosidicus gigas) By-Products - Yeromi Coral Paredes Llosa; Klidem Francisco Velazquez Carlier; Nancy Chasquibol (Biology and Life Sciences Forum)
In recent years, consumers have been increasingly concerned about their health. Therefore, the snack market is rapidly developing more innovative and functional products such as cereal bars. Quinoa (Chenopodium quinoa) and kiwicha (Amaranthus caudatus) are Andean pseudocereals with protein (10.90–11.35%) content and other functional components that reduce the risk of cardiovascular diseases and inflammatory illnesses. Peru is the world’s second largest exporter of Pota (Dosidicus gigas), with 476.5 million metric tons in 2023; however, only between 50% and 70% of it has been taken advantage of. Pota by-products such as skins, viscera, and necks have significant protein content (70%) and are discarded. In this investigation, cereal bar formulations with Pota by-products and Andean pseudocereals were optimized and characterized using a five-run simplex centroid mixture design. The effects of two independent variables were examined, namely collagen (2–8%) and binders (22–28%), on the sugar (%), protein (%), and antioxidant (µg Trolox/g dry weight, dw) content as response variables. The optimized cereal bar (M6) showed high protein (21.27 ± 1.51%) content, moisture (10.37 ± 0.04%), ash (2.57 ± 0.03%), fat (15.12 ± 0.15%), carbohydrates (53.67 ± 1.70%), total polyphenol (1570 ± 267 µg Gallic acid equivalent/g dw) content, antioxidant activity (1656 ± 77 µg Trolox/g dw), essential amino acid–leucine (15.65 ± 1.83 mg/g protein) content, and higher in vitro digestibility (78.78 ± 1.40%) than the control sample. The cereal bar had a positive sensory acceptability (88.89%) and complied with Peruvian standards. The functional bar emerges as a nutritious alternative in the food industry and proposes a sustainable solution using Pota by-products, fostering a circular economy.